An Analysis Of Students Speaking Skill In Presenting Procedure Text - Siti Qaulan Layyina; Yessy Marzona; Sherly Franchisca (JURNAL ARMADA PENDIDIKAN, 2025)
This research was due to several speaking problems faced grade X students at SMKN 6 Padang in their English class, particularly in presenting procedure texts. The research employed a descriptive method with a population of 100 tenth-grade Culinary students, from which one class (X KUL 3, consisting of 30 students) was selected through cluster random sampling. Data were collected using a speaking test where students presented procedure texts they had created, and their performances were evaluated using a standardized speaking rubric. The findings showed that most students’ speaking ability in class X KUL 3 was categorized as moderate, with a mean score of 61.4. Despite this, several difficulties were still evident, especially in pronunciation and fluency, which affected 83.3% of the students. Other challenges included limited vocabulary and low interest in learning English. Overall, the results highlight the need for greater support in enhancing students’ speaking performance, particularly in overcoming pronunciation and fluency problems to help them achieve more advanced levels of proficiency.